Activated Protein C Sensitivity, Protein C, Protein S and Coagulation in Normal Pregnancy - Clark, P.; Brennand, J.; Conkie, J. A.; McCall, F.; Greer, I. A.; Walker, Isobel D. (Thrombosis and Haemostasis, 1998)
A prospective study of activated protein C sensitivity, protein C, protein S, and other coagulation factors in 239 women during normal pregnancy was carried out. Protein C activity appeared unaffected by gestation, although an elevation of protein C activity was observed in the early puerperium. A fall in total and free protein S with increasing gestation was observed. Activated protein C sensitivity ratio (APC:SR) showed a progressive fall through pregnancy. This fall correlated with changes in factor VIIIc, factor Vc and protein S. 38% of subjects, with no evidence of Factor V Leiden or anticardiolipin antibodies, showed a low APC:SR (APC:SR <2.6) in the third trimester of pregnancy. Aside from a significant reduction in birth weight, no difference in pregnancy outcome was observed between these subjects and those with a normal APC:SR. Activated protein C sensitivity ratio, modified by pre-dilution of patient samples with factor V depleted plasma, showed no consistent trend with gestation.